ANALISIS PENGARUH KEPEMIMPINAN KYAI, BUDAYA PESANTREN, DAN MOTIVASI KERJA GURU TERHADAP MUTU PENDIDIKAN PESANTREN DI PROVINSI BANTEN - Suhendar, Suhendar; Soedjarwo, Soedjarwo; Basuki, Ismet (Universitas Negeri Semarang, 2017)
This study explains the direct and indirect effects of kyai leadership quality on the quality of pesantren education seen from teacher and kyai perspective as measured through leadership, pesantren culture and teacher work motivation. This research is a quantitative research using survey method and Partial Least Square (PLS) analysis technique. The research subjects were 32 pesantren in Banten Province and with 192 respondents consisting of 32 kyai and 160 teachers. The study found that the leadership quality of kyai had only a direct effect on pesantren culture and teacher work motivation, but did not have a direct effect on the quality of pesantren education. The quality of kyai leadership has an indirect effect on the quality of pesantren education through pesantren culture and teacher work motivation. This research is in line with the leadership theory of paternalistic-free rein leadership and charismatic-traditional-rational, which leads to the quality of kyai leadership has no direct effect on the quality of pesantren education in Banten Province.